Pressure-induced structural change in liquid GeI4. (27th December 2017) - Fuchizaki, Kazuhiro; Nishimura, Hironori; Hase, Takaki; Saitoh, Hiroyuki
Abstract: The similarity in the shape of the melting curve of GeI4 to that of SnI4 suggests that a liquid–liquid transition as observed in liquid SnI4 is also expected to occur in liquid GeI4 . Because the slope of the melting curve of GeI4 abruptly changes at around 3 GPa, in situ synchrotron diffraction measurements were conducted to examine closely the structural changes upon compression at around 3 GPa. The reduced radial distribution functions of the high- and low-pressure liquid states of GeI4 share the same feature inherent in the high-pressure (high-density) and low-pressure (low-density) radial distribution functions of liquid SnI4 . This feature allows us to introduce local order parameters that we may use to observe the transition. Unlike the transition in liquid SnI4, the transition from the low-pressure to the high-pressure structure seems sluggish. We speculate that the liquid–liquid critical point of GeI4 is no longer a thermodynamically stable state and is slightly located below the melting curve. As a result, the structural change is said to be a crossover rather than a transition. The behavior of the local-order parameters implies a metastable extension of the liquid–liquid phase boundary with a negative slope.